AI-Powered POCUS Ultrasound for Rapid and Accurate Deep Vein Thrombosis Detection - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Discover how AI-enabled POCUS ultrasound improves rapid and accurate deep vein thrombosis detection, enhancing emergency care and reducing diagnostic time.
Keywords: Deep Vein Thrombosis; POCUS Ultrasound; Artificial Intelligence; Medical Imaging; Emergency Medicine